U–Pb zircon geochronology of the eastern part of the Southern Ethiopian Shield - Stern, R.; Ali, K.; Abdelsalam, M.; Wilde, Simon; Zhou, Q. (Elsevier BV, 2012)
The Southern Ethiopian Shield (SES) in the central East African Orogen lies at the junction of Neoproterozoic (880–550 Ma) largely greenschist-facies juvenile crust of the Arabian-Nubian Shield in the north and more metamorphosed and remobilized older crust of the Mozambique Belt to the south.The SES exposes a polycyclic sialic gneissic basement (represented by the Alghe Terrane in this study) with interleaved ophiolitic–volcano–sedimentary (Kenticha, Megado, and Bulbul) terranes. U–Pb zircon SHRIMP and LA-ICP-MS dating of 8 igneous and metamorphic intermediate and felsic bodies in the eastern SES yield Neoproterozoic crystallization ages: 847 ± 11, 855 ± 14, 732 ± 5, 665 ± 8, 657 ±6, 560 ± 8, and 548 ± 8 Ma. From these and previously published ages, we infer 4 principal magmatic episodes: 840–890 Ma (Late–Tonian–Early Cryogenian), 790–700 Ma (Cryogenian), ~660 Ma (Moyale Event), and Pan-African (630–500 Ma; Ediacaro-Cambrian). Neoproterozoic zircon xenocrysts (941, 884, 880, 863, 762, 716 and 712 Ma) confirm the dominance of Neoproterozoic crust in the study area.One sample of undeformed granite from the Alghae Terrane has abundant Archean zircons and may be a ~550 Ma melt of ~2.5 Ga crust, demonstrating for the first time that Archean crust or sediments with abundant Archean zircons exists in the SES. In spite of ~300 million years of Neoproterozoic igneous activity, we see no evidence of systematic compositional evolution in SES igneous rocks from early low-K suites to late high-K suites. Ediacaran deformation and magmatism of the SES reflects Late Tonian and Cryogenian formation of mostly juvenile crust that was subsequently deformed and chemically modified as a result of collision between large fragments of East and West Gondwana. Terminal collision began at ~630 Ma and caused crustal thickening, melting, uplift, erosion, orogenic collapse, and tectonic escape over a broad region of the East African Orogen, including up to ~25 km of erosion of SES crust. Plate convergence was likely continuous from ~630 Ma, forming major N-S structures. Deformation stopped at ~550 Ma and was followed by exhumation between ~530 and 500 Ma.